Utilization Of The Puppet Stage As A Method Of Contextual Evangelism To Sunday School Children Aged 5-10 Years - Agnes Alicia; Ayu Rotama Silitonga; Agustina Bela; Ayang Emiyati (Jurnal Didaskalia, 2020)
Children's ministry is very motivating for the church and child servants because it affects the growth of the child's faith. One of them is the ministry of evangelism. Evangelism is the message of salvation and judgment in Christ Jesus. Children aged 5 - 10 years do not usually understand and interpret themselves as "Christians" because they only follow what their parents do and do. = 'So it is necessary to teach through evangelism to these children. The question is how does a minister convey the "gospel" message to children so that it can be understood easily and what are the results of the ministry? This paper has two purposes. First, the servant understands the method or way of a servant to convey the "gospel" message simply. Second, so that children better understand the true meaning of the Bible. The research method used is qualitative by interviewing sources to examine and understand the attitudes, views, feelings and behavior of an individual or group of people and literature research to support this writing.